From screens to scores: attitudes towards social media and its impact on medical students’ mental health and learning - Shah, Dev K.; Modna, Yuliya; Scott, Bernadette (International Journal of Research in Medical Sciences, 2025)
Background: Medical students frequently use social media for both personal and professional purposes. While it can enhance learning and reduce loneliness, it also poses risks such as anxiety and depression. This study explores usage patterns, attitudes, and impacts on their mental health and learning. Methods: Preclinical students completed an anonymous questionnaire covering demographics, social media usage, attitudes towards social media in medicine, and mental health assessment via the hospital anxiety and depression scale (HADS). Results: Out of 175 students, 126 completed the questionnaire. Most spent 1-5 hours daily on 2-5 social media platforms, with older students spending less time online. The most popular platforms were Instagram, WhatsApp, and YouTube. About 30.2% used social media solely for personal purposes, while 69.8% used it for both personal and professional activities. Most participants found social media useful for learning and professional growth but had ethical concerns. Nearly half of the participants reported no academic impact from social media use, 37.3% reported negative effects, and 14.3% valued positive effects. A weak positive correlation was found between social media usage and anxiety, but not depression. Conclusions: Social media shapes educational paradigms, enhancing medical students’ learning, collaboration, and professional growth. Perceptions of social media’s impact on academics varied among participants, but neither these perceptions nor the time spent on social media significantly affected GPA. The study found a link between social media use and anxiety, but not depression. Understanding these dynamics is crucial for supporting students’ mental health and academic success in the digital age.